2015
DOI: 10.4103/1735-3327.161422
|View full text |Cite
|
Sign up to set email alerts
|

Interforaminal hemorrhage during anterior mandibular implant placement: An overview

Abstract: Implant surgery in mandibular anterior region may turn from an easy minor surgery into a complicated one for the surgeon, due to inadequate knowledge of the anatomy of the surgical area and/or ignorance toward the required surgical protocol. Hence, the purpose of this article is to present an overview on the: (a) Incidence of massive bleeding and its consequences after implant placement in mandibular anterior region. (b) Its etiology, the precautionary measures to be taken to avoid such an incidence in clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 40 publications
0
4
1
Order By: Relevance
“…According to a study by Romanos GE et al 2012, panoramic radiograph can detect only 2.7% of lingual foramen. 16 However, incidence reported on CBCT ranges from approximately 85-100% according to studies by Makris N et al, Kusum CK et al, Denny CE et al [17][18][19] In the present study a low incidence of 45% was observed. One possible interpretation for this disagreement could be the imaging technique used.…”
Section: Discussioncontrasting
confidence: 44%
“…According to a study by Romanos GE et al 2012, panoramic radiograph can detect only 2.7% of lingual foramen. 16 However, incidence reported on CBCT ranges from approximately 85-100% according to studies by Makris N et al, Kusum CK et al, Denny CE et al [17][18][19] In the present study a low incidence of 45% was observed. One possible interpretation for this disagreement could be the imaging technique used.…”
Section: Discussioncontrasting
confidence: 44%
“…Intraoral bleeding is a very serious situation when it obstructs the airway [6] . Previous reports [19] suggest that small blood vessels with a diameter <1 mm are rarely problematic when resecting these blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Damage to neurovascular canals and foramens in the mandible during oral surgical procedures causes many complications, the most serious of which are sensory disturbances and bleeding [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the proximity of the blood vessels to the lingual cortical plate of the mandibular midline, there is a risk of surgical trauma in implant placement in this region since even a very small perforation of the mandibular cortical plate may cause bleeding [23]. The most likely reason for a haemorrhage is bleeding from a sublingual artery or its branches, secondary to lingual cortex perforation during osteotomy preparation for implant placement [11]. Woo et al [24] report a case of haemorrhage resulting from an incision made too far lingual from the alveolar crest; the dissection was carried out supraperiosteally, resulting in laceration of the sublingual artery and hypoglossal nerve.…”
Section: Discussionmentioning
confidence: 99%
“…These arteries may lie superficially in atrophic cases and can be an important source of haemorrhage if traumatised during implant placement. Haemorrhages in the anterior mandibular region (immediate or delayed) caused by implant placement may lead to serious respiratory complications even including death of the patient [11].…”
Section: Introductionmentioning
confidence: 99%